Power sharing analysis of a new modified multi-input interleaved boost converter based on H-Bridge cells - Yonis. M, Yonis Buswig; W. M., Utomo; Z. A., Haron; A., Bakar (Asian Research Publishing Network (ARPN), 2016)
In this paper, a new modified multi-input boost converter is proposed using H-bridge cells as building blocks and uncoupled inductors in parallel using interleaved technique as ripple reduction method. The objectives of this paper are to design a high ripple reduction and a high-performance multi-input boost converter. Different operating modes and the switch realization of the new converter are obtained. The modes of operation based on the status of the four switches. The proposed multi-input boost converter is composed of two inputs source that accommodated with some extra semiconductors, inductances and diodes to form the interleaving technique as proposed method. The proposed concept has been investigated through simulation using the MATLAB/Simulink environment. The simulation results confirm the validity of the proposed method, which can be seen as a promising new topology that ensure multi-input converter suitable for renewable energy applications